1993
DOI: 10.1007/bf01146169
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polycyclic aromatic hydrocarbons in the lung

Abstract: Polycyclic aromatic hydrocarbons (PAHs) accumulated in human lung samples from men (n = 236) and women (n = 128) were determined by high-performance liquid chromatography (HPLC) to examine their association with lung cancer. The mean values for benzo[a]pyrene (BaP), benzo[k]fluoranthene (BkF), and benzo[g,h,i]perylene (BghiP) in lungs (ng/g dry lung) of Japanese autopsied patients were 0.54, 0.44, and 0.87, respectively. The modal values were 0.3, 0.3 and 0.5, respectively. Each of the PAH concentrations was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…As environmental pollution progresses, the amount of chemical carcinogen chronically inhaled by the exposed human population will also increase. In particular, PAHs (such as methylcholanthrene) are globally distributed environmental pollutants known for their carcinogenic and mutagenic effects on humans (42)(43)(44)(45). Fibroblasts are also present in human tissues exposed to carcinogen as, for example, asbestosis, making it important to study if encapsulation of carcinogen can be found in humans, especially in the light of the report from the International Agency for Research on Cancer (Lyon, France) that diesel engine exhaust is definitely carcinogenic to humans (a group 1 carcinogen, which is actually the same category as methylcholanthrene; refs.…”
Section: Discussionmentioning
confidence: 99%
“…As environmental pollution progresses, the amount of chemical carcinogen chronically inhaled by the exposed human population will also increase. In particular, PAHs (such as methylcholanthrene) are globally distributed environmental pollutants known for their carcinogenic and mutagenic effects on humans (42)(43)(44)(45). Fibroblasts are also present in human tissues exposed to carcinogen as, for example, asbestosis, making it important to study if encapsulation of carcinogen can be found in humans, especially in the light of the report from the International Agency for Research on Cancer (Lyon, France) that diesel engine exhaust is definitely carcinogenic to humans (a group 1 carcinogen, which is actually the same category as methylcholanthrene; refs.…”
Section: Discussionmentioning
confidence: 99%
“…They are formed from the incomplete pyrolysis of tobacco leaves and many types of PAHs are present in tobacco smoke as a complex mixture. Parent PAHs can be detected in human lung tissue (Lodovici et al, 1998;Seto et al, 1993). PAHs are metabolically activated in humans through CYP1A1, CYP1B1 and CYP3A4 (Kim et al, 1998;Shimada et al, 1996), and conjugated for excretion by glutathione-S-transferases, sulfuronyl transferases and glucuronyl transferases (Robertson et al, 1988).…”
Section: Exposure To Tobacco Carcinogensmentioning
confidence: 99%
“…Using a large sample population, total PAH levels in lung tissue has also been shown to correlate to cancer incidence (Seto et al 1993).…”
Section: Health Effectsmentioning
confidence: 99%